Likely Effects of Geological Features on Carbonate Rock Strength - Arman, Hasan; Hussein, Saber; Alshehyari, Shamma Khalfan; El Imam, Hiba Hashim; Alhaj, Asmaa Ahmad; Albedwawi, Maryam Ali (Review of Environment and Earth Sciences, 2018)
Rock strength is commonly recognized as a rock ability to resist stress or deformation without breaking down. Its measurement in either in-situ or laboratory environment is costly and requires time-consuming efforts for rock sampling, preparation and laboratory tests. There are different suggested testing methods available such as Unconfined Compressive Strength (UCS), Point Load Index (PLI), Indirect Tensile Strength (ITS), Schmidt Hammer Rebound (SHR), etc. and used to interpret of rock strength properties. The study will only focus on carbonate rocks (Upper Eocene Dammam Formation) which were collected from different selected sites in the Hafeet Mountain area, Al Ain city, United Arab Emirates. Following the sample preparations based on the ASTM standards, about fourth UCS, fourth-one ITS, thirty-seven PLI and hundreds to thousands of SHR tests were carried out on rock blocks and core samples according to ASTM Standards. The study indicates that the relationships between UCS and PLI, ITS, SHR of limestone can be estimated using the simple linear mathematical equations. However, the results exhibit a weak to weaker linear correlation with highly scattered data. This may be due to sample heterogeneity and nature of the sample. Therefore, it still needs better confirmation with more samples from different locations in order to use confidently in engineering applications.